Exploring Yaoundé as a Linguistically Divided Capital City of an English and French Bilingual African Nation - Dassé, Théodore (Text Matters: A Journal of Literature, Theory and Culture, 2025)
This article examines the place of translation in the public space in Yaoundé, the capital city of Cameroon, an African nation with a threefold (German, English, and French) colonial heritage. The collected quantitative and qualitative data consisted of public space literature, i.e. outdoor advertising in the streets and other urban spaces where francophone and anglophone communities interact. Data analysis combined with the theory of translationality proposed by Sherry Simon in 2014 and 2021 revealed that Yaoundé is not a dynamic translation zone, because the translational activity in this urban space is minimal. Instead, Yaoundé is almost distinctively monolingual in French and English, and quasi-untranslated. This quasi-absence of translation-mediated contact between the communities makes Yaoundé a linguistically divided city, where French-speaking and English-speaking citizens live in juxtaposition and co-exist in relative isolation. This adversely impacts the traffic of information and opportunities across linguistic borders.